EDUKASI IBU-IBU TERKAIT BAHAYA MERKURI PADA KOSMETIK PEMUTIH DI BONTOALA TUA KECAMATAN BONTOALA KOTA MAKASSAR - Rahma wati; Anita .; Muawanah .; Andi Fatmawati; Hasnah . (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2022)
One of the cosmetics that is widely used by the general public, especially women, is facial whitening. Some manufacturers are not responsible for using harmful substances such as mercury (Hg) is used as a skin whitening agent. It can damage organs over time and is also highly toxic. Mercury can be toxic in small amounts. Side effects start with skin discoloration, darkening, allergies and inflammation, high doses can cause permanent damage to the brain and kidneys as well as cause fetal damage. Short-term exposure to high doses can cause vomiting, diarrhea, lung damage and is a carcinogen. This community service activity is very important because the community needs to be protected from the circulation of cosmetics that do not meet the safety, benefit and quality requirements. Cosmetics containing heavy metals that exceed the requirements can harm and endanger public health. The purpose of this community service activity is to increase awareness and understanding of the importance of choosing safe cosmetics for mothers so that it is expected to have benefits for increasing knowledge and awareness about cosmetics, as well as mothers. -Mother has the will and ability to choose cosmetics that are safe for health. Participants were so enthusiastic in participating in the material delivery event, this was because there had never been any counseling related to the safe use of cosmetics. After participating in this outreach activity, participants are expected to understand cosmetic standards that are safe from harmful heavy metals such as mercury, choose good cosmetics, and know the shelf life and proper storage of cosmetics.